KEPEMIMPINAN DAN PERILAKU KREATIF Suatu upaya Mengelaborasi Keterpaduan Gagasan Para Individu - AMIRULLAH - (STIE Indonesia Malang, 2016)
This article aims to explain the important role of a leader in connection with theformation of individual creative behavior. Leadership has a huge role for theinitiative and motivation of the idea of the individual in achieving creativity, onthe other hand the characteristics of individual creativity is a function for theemergence of creative behavior and creativity of the individual. Successful leadersdo not just become a creative, but more than that he should be able to developcreative behavior followers. Base role of a leader is to coordinate the activities ofthe individual as a process without coercive influence that resulted in theacceptance or commitment and adaptability, so that they can contribute to theobjectives of the organization. The responsibility of a leader is to help developvalue creation by combining various differences or divergence of interests amongindividuals.Keywords: leadership, creative behavior, individual creativity